Canoe and canvas : life at the encampments of the American Canoe Association, 1880-1910 - Dunkin, Jessica, 1981- (University of Toronto Press, 2019)
"Canoe and Canvas: Life at the Encampments of the American Canoe Association, 1880-1910 offers a detailed portrait of the summer encampments of the American Canoe Association between 1880 and 1910. The encampments were annual events that attracted canoeing enthusiasts from both sides of the Canada-US border to socialize, race canoes, and sleep under canvas. While the encampments were located away from cities, they were still subjected to urban logics and ways of living. The encampments, thus, offer a unique site for exploring cultures of sport and leisure in late Victorian society, but also for considering the intersections between recreation and the politics of everyday life. A social history of sport, Canoe and Canvas is particularly concerned with how gender, class, and race shaped the social, cultural, and physical landscapes of the ACA encampments. Although there was an ever-expanding arena of opportunity for leisure and sport in the late nineteenth century, as the example of the ACA makes clear, not all were granted equal access. Most of the members of the American Canoe Association and the majority of the campers at the annual encampments were white, middle-class men, though white women were extended partial membership in 1882, and in 1883, they were permitted to camp on site. Canoe and Canvas also reveals how Black, Indigenous, and working-class people, while obscured in the historical record, were indispensable to the smooth functioning of these events through their labour."--